PENANAMAN NILAI-NILAI KARAKTER ISLAMI MELALUI PROGRAM BPI (BINA PRIBADI ISLAM) DI SMPIT AL KHOIRIYAH GARUT - Wati Karmila; Uci Tarmana (Al-Hasanah : Jurnal Pendidikan Agama Islam, 2021)
The purpose of this study in general is to analyze and find out the cultivation of Islamic character values ​​through the BPI (Islamic personal development) program at SMPIT Al Khoiriyah Garut. This study uses a qualitative approach with analytical descriptive method. Data collection techniques using observation, interviews, and documentation studies. While the data analysis uses data reduction, data display and data conclusions. The results of this study indicate that: 1) The purpose of instilling Islamic Character Values ​​through the BPI (Islamic Personal Development) Program at the Al-Khoiriyyah Integrated Islamic Junior High School, namely to cultivate Islamic habits and good morals that are in accordance with the guidance of Islamic teachings for students continuously in everyday life so that later students are ready to enter the community as a superior generation who is intelligent, independent and religious/spiritual. While the programs are: Tahsinul and Tahfidzul Qur'an Learning, Extracurricular Programs, Addition of Local Content, Parents School Activities, and Boarding School Programs that are in dormitories 2) Implementation using exemplary coaching approaches, oaching with habituation, and coaching with advice that goes into the program and included in the learning time 3) The results have a positive impact by speaking in polite language and doing good to others, always covering the genitals, learning amar ma'ruf nahi munkar, doing ablution in an orderly and correct manner, praying in congregation, memorizing Al-Qur'an and its translation and the hadith of the Prophet which are applied in everyday life.